2015
DOI: 10.1080/10447318.2015.1064658
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Usability of Mobile Applications for Phones and Tablets

Abstract: The use of applications on mobile devices has reached historic levels. Using the System Usability Scale (SUS), data were collected on the usability of applications used on two kinds of mobile platforms-phones and tablets-across two general classes of operating systems, iOS and Android. Over 4 experiments, 3,575 users rated the usability of 10 applications that had been selected based on their popularity, as well as 5 additional applications that users had identified as using frequently. The average SUS rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
6
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(94 citation statements)
references
References 37 publications
6
80
6
2
Order By: Relevance
“…This corresponds to a score of “average” per SUS guidelines, which indicates that student learning of neuroscience concepts was not impeded by usability issues. Although the SUS was not originally designed for testing the usability of mobile-based technology, studies have shown that SUS scores for mobile applications in the range 67.7 – 87.4 are typical of apps considered to be top-10 across all app categories (Kortum & Sorber, 2015). Overall scores on the system usability scale did not differ significantly between conditions, which was tested using a one-way ANOVA: F (3) = 0.529, p = .663, indicating that the comparisons of student learning by experimental condition were not affected by any differences in perceived usability.…”
Section: Resultsmentioning
confidence: 99%
“…This corresponds to a score of “average” per SUS guidelines, which indicates that student learning of neuroscience concepts was not impeded by usability issues. Although the SUS was not originally designed for testing the usability of mobile-based technology, studies have shown that SUS scores for mobile applications in the range 67.7 – 87.4 are typical of apps considered to be top-10 across all app categories (Kortum & Sorber, 2015). Overall scores on the system usability scale did not differ significantly between conditions, which was tested using a one-way ANOVA: F (3) = 0.529, p = .663, indicating that the comparisons of student learning by experimental condition were not affected by any differences in perceived usability.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the distribution of the devices and browsers used. This information is also valuable as the perceived usability could depend on the device used for the access [45], and even the System Usability Scale score could be afflicted by the context [46].…”
Section: P O S Tmentioning
confidence: 99%
“…Students who used mobile devices in collaborative environments vs. desktops self-reported a more positive effect in their flow experience than the students that used desktops (Abrantes and Gouveia, 2010). Recent studies have shown that applications on smartphones were judged to be more usable than applications on other platforms (Kortum, and Sorber, 2015). The portability and ease of use mobile characteristics highly influence smartphone usage over desktop computers (Adepu and Adler, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%